Prediksi Hujan Menggunakan Metode Artificial Neural Network, K-Nearest Neighbors, dan Naïve Bayes - Martha, Regina; Herwindiati, Dyah Erny (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2024)
Rain is a natural phenomenon that has a significant impact on human life and ecosystems around the world. The ability to predict the weather, including predicting the next day's rain, has become an important aspect of our daily lives. Accurate rain predictions have broad implications, from planning outdoor activities to natural resource management, as well as controlling natural disasters. This research presents the results of an analysis of whether it will rain or not tomorrow based on 22 features, including location, temperature, wind speed, wind direction, humidity, and also the number of clouds covering the sky. In an effort to improve the accuracy of rain predictions, various methods have been developed, including Artificial Neural Network (ANN), K-Nearest Neighbors (KNN), and Naive Bayes. After training and testing the models from these three methods, an evaluation was carried out using a confusion matrix and classification report to measure prediction performance. The experimental results show that ANN, KNN and Naive Bayes obtain accuracy scores of 85%, 84%, and 79%, respectively. So, it can be concluded that ANN is the best method for predicting tomorrow's rain.